The Development of an Instructional Model to Improve Student Feedback Literacy in Blended Learning Environments at Vocational Colleges in Guangxi, China - Li, Xiaomin; Reed Merritt, Matthew (Asia Pacific Journal of Religions and Cultures, 2024)
The impact of providing feedback on student performance has been possessed the potential to yield substantial enhancements in learning outcomes. This study aimed to develop an instructional model to improve student feedback literacy at a vocational college in Guangxi, China. The acquisition of qualitative data involved conducting an extensive literature review, which was subsequently scrutinized to integrate the indispensable skills and the strategies influencing student feedback literacy. A questionnaire was created and circulated among 1203 students in three vocational colleges, with the aim of gathering quantitative data. The findings showed high levels of student feedback literacy in the three targeted schools, Mean 3.63, S.D. .995. Simultaneously, the strategies that influence student feedback literacy were found to be online and offline teacher feedback, online and offline peer feedback, feedback files, and authentic feedback. The findings of the survey also indicated a positive correlation between the aforementioned six strategies and the enhancement of student feedback literacy.